Acceptance of oil palm smallholders toward supervised farm credit scheme at area farmer organization, Muar Selatan, Johor / Ridduan Ismail - Ismail, Ridduan (Faculty of Plantation and Agrotechnology, 2017)
The purpose of this study is about acceptance of oil palm smallholders toward supervised farm credit scheme. The objective was to identify the factors that influence smallholders to accept supervised farm credit scheme. This study applied the survey study where questionnaire distributed to the selected location of study. This study was conducted among smallholder at Area Farmer Organization, Muar Selatan and the total respondent are 73 people. By using the questionnaire, the data and information was collected and analyzed. The result for reliability statistic is .685. It means the data is acceptable. Based on Spearman’s correlation analysis table, the strength of relationship between agreement and acceptance has been classified as weak positive correlation because value of r=.238. The regression analysis showed that agreement was significantly influenced acceptance of SKLT,(β1=0.188; t-value=7.590; p<0.05). Therefore, H1 was support dependent variable, agreement had significant relationship with acceptance of SKLT. The suggestion is smallholder have fairly standardized mechanisms for interaction with AFO’s and next is to deepen and broaden to documentation of examples of successes and failures in management mechanisms.